The User IS the Enemy, and (S)he Keeps Reaching for that Bright Shiny Power Button! - Schechter, Stuart (Proceedings of the Workshop on Home Usable Privacy and Security (HUPS), 2013)
Children represent a unique challenge to the security and privacy considerations of the home and technology deployed within it. While these challenges posed by children have long been researched, there is a gaping chasm between the traditional approaches technologists apply to problems of security and privacy and the approaches used by those who deal with this adversary on a regular basis. Indeed, addressing adversarial threats from children via traditional approaches to computer and information security would be a recipe for disaster: it is rarely appropriate to remove a child’s access to the home or its essential systems; children require flexibility; children are often threats to themselves; and children may use the home as a theater of conflict with each other. Further, the goals of security and privacy must be adjusted to account for the needs of childhood development. A home with perfect security – one that prevented all inappropriate behavior or at least ensured that it was recorded so that the adversary could be held accountable – could severely stunt children’s moral and personal growth. We discuss the challenges posed by children and childhood on technologies for the home, the philosophical gap between parenting and security technologists, and design approaches that technology designers could borrow when building systems to be deployed within homes containing this special class of user/adversary.